COVID-19 Stigmatization: Concept Analysis - Dag, Sinem; Hazir, Guenay; Guevenc, Guelten; Iyiguen, Emine (Galenos Publ House, 2021)
The new coronavirus disease (COVID-19) is spreading rapidly worldwide and has been declared as a pandemic in 2020. Countries have taken many measures against the pandemic. However, the spread of the virus could not be entirely slowed down. People who are diagnosed with COVID-19 and their families, healthcare workers, citizens of countries in the Far East, the elderly, and people who travel are stigmatized. Stigmatization can have a negative effect on individuals, families, and on society. Discrimination as a result of stigma prevents people in society from receiving proper care and treatment and leads to psychological problems. Stigma should be prevented to mitigate the effects of COVID-19. The objective of this study was to analyze the concept of COVID-19 stigma. This concept was analyzed with the Walker and Avant concept analysis method. In literature review, articles that are accessible and relevant for concept analysis were found by found about COVID-19 stigma concept analysis in literature. Therefore, this COVID-19 stigma concept analysis will provide guidance to healthcare professionals.
Keywords: COVID-19; SARS-CoV-2; stigma; concept analysis